Chapter Precision agriculture and conservation of coastal landscapes - D'Antonio, Chiara (Proceedings e report, 2020)
The application of Precision Agriculture strategies represents an opportunity for farmers to obtain economic benefits. In the area of Metapontino, as demonstrated by the experimentation conducted, the challenge of producing food and at the same time protecting nature and safeguarding biodiversity, it is possible to face it through the introduction of global positioning systems (GPS), a technology capable of integrating the information on soil type, climate, cultivar, crop and farm management, topography and economy.